Study on the Computational Nutraceutics of a Citrus Flavonoid: An Approach Using Conceptual Density Functional Theory (CDFT) - Flores-Holguin, Norma; Frau, Juan; Glossman-Mitnik, Daniel (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
The objective of this research is to assess the M06 family of density functionals for the calculation of the molecular structure and properties of the Naringin flavonoid and to calculate the chemical reactivity descriptors using the Conceptual DFT (CDFT) methodology. The active sites for the nucleophilic and electrophilic attacks have been determined by relating them to the Fukui function indices and the dual descriptor f (2)(r). A comparison between the descriptors calculated through vertical energy values and those arising from the Koopmans’ theorem approximation has been performed as a further check of the validity of the last procedure.